The role of prolactin in the control of ovine lactogenesis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University - Peterson, Samuel Walter (Massey University. Institute of Veterinary, Animal and Biomedical Sciences, 1992)
A series of trials was carried out to examine the role of prolactin (PRL) in the control of lactogenesis in New Zealand Romney x Border Leicester ewes. In addition, a study was made of differences in milk yields and plasma PRL concentrations between spring- and autumn-lambing ewes.Daily subcutaneous injections of 2 mg CB154 inhibited PRL secretion and delayed lactogenesis. There were no consistent effects on plasma progesterone or insulin concentrations. CB154 treatment was more effective in reducing milk yield in twin-bearing than in single-bearing ewes when used for 20 days than for 9 days prepartum. The differential effects on milk yield cannot be explained by corresponding effects on plasma PRL or insulin concentrations. Circulating PRL during the period 20 to 10 days prepartum may have an important effect on milk yield in twin- but not single-bearing ewes.Subcutaneous injections of 0.5 mg/kg live weight oPRL, administered on 2 consecutive days peripartum, to ewes treated with CB154 for 7 days prepartum, resulted in milk yields similar to those in control ewes and significantly (P<0.01) greater than those in ewes treated with CB154 alone. This indicated that oPRL prevented the CB154-induced reduction of milk yields and has established that the effect of CB154 on lactogenesis is mediated through suppression of PRL secretion and not by effects on some other hormone.Injection of 10 mg oPRL directly into one mammary gland (via the teat duct) increased milk yields relative to the contralateral, bicarbonate-treated gland in CB154-treated ewes. The intramammary oPRL injection did not raise circulating PRL concentrations. Furthermore, the milk yields of bicarbonate-treated glands in ewes treated with bicarbonate only, did not differ from those of bicarbonate-treated glands in ewes treated with oPRL in the contralateral gland, demonstrating that there were no effects of oPRL, transferred via the circulation from the treated gland, on the contralateral gland. Glands treated with oPRL produced 15% (P<0.05) more milk than the bicarbonate-treated glands during the first 8 days of lactation and the difference was maintained throughout the 8-week lactation period, indicating that the oPRL had effected a permanent change in the ability of the gland to produce milk. It is concluded that PRL acts directly on the mammary gland without the need for a putative intermediate hormone, and that intramammary PRL concentrations during lactogenesis may have long-lasting effects on lactation.The possibility was examined that dietary differences were responsible for seasonal differences in plasma PRL concentrations, milk yields, milk composition, lamb birthweight and lamb growth rate, observed in earlier trials. Mean plasma PRL levels were significantly (P<0.01) higher in spring- (192±38 ng/ml) than in autumn- (71±17 ng/ml) lambing ewes housed indoors under constant photoperiod (18L:6D) and fed the same diet. Milk yields were also significantly (P<0.05) higher in the spring- (2041±114 g/d) than in the autumn- (1563±109 g/d) lambing ewes over the 8 day lactation. Lamb growth rates (adjusted for birthweight, birthrank and sex of lamb) from birth to 8 weeks of age were significantly (P<0.001) higher in spring (282±12 g/d) than in autumn (225±15 g/d). The seasonal differences were confounded with corresponding differences in ewe live weight and it was not possible to determine whether dietary differences contributed significantly to the differences observed.Two routes of oPRL supplementation were used to test the effectiveness of elevating peripheral or local levels of PRL in autumn-lambing ewes which, based on previous results, were expected to have low plasma PRL concentrations and milk yields relative to spring-lambing ewes. Administration of 10 mg supplementary oPRL directly into the gland or subcutaneous injection of 0.5 mg/kg oPRL did not increase the milk yields, or change the composition of milk, compared to controls. These results suggest that the circulating level of PRL, and the intramammary concentration of PRL, in autumn-lambing ewes are not limiting lactogenesis. Because the plasma prolactin concentration in the ewes was unexpectedly high, it was not possible to reach firm conclusions regarding possible effects of supplementary oPRL in ewes with naturally low plasma PRL concentrations. Nevertheless, the results indicate that raising the intramammary concentration of PRL around the time of parturition, in ewes with circulating PRL levels characteristic of normal spring-lambing ewes, does not enhance lactogenesis.It is concluded that PRL is important to the complete initiation of lactogenesis in ewes, that it acts directly on the gland and that it is necessary for establishing the maximum potential of the gland to secrete milk.
Keywords: Prolactin; Lactogenesis; Sheep; Milk; Bromocriptine; 300505 Anatomy and physiology